Phytochemical and Nutraceutical Screening of Ethanol and Ethyl Acetate Phases of Romanian Galium verum Herba (Rubiaceae) - Alexandra-Denisa Semenescu; Elena-Alina Moacă; Andrada Iftode; Cristina-Adriana Dehelean; Diana-Simona Tchiakpe-Antal; Laurian Vlase; Ana-Maria Vlase; Delia Muntean; Raul Chioibaş (Molecules, 2023)
Galium species are used worldwide for their antioxidant, antibacterial, antifungal, and antiparasitic properties. Although this plant has demonstrated its antitumor properties on various types of cancer, its biological activity on cutaneous melanoma has not been established so far. Therefore, the present study was designed to investigate the phytochemical profile of two extracts of G. verum L. herba (ethanolic and ethyl acetate) as well as the biological profile (antioxidant, antimicrobial, and antitumor effects) on human skin cancer. The extracts showed similar FT-IR phenolic profiles (high chlorogenic acid, isoquercitrin, quercitrin, and rutin), with high antioxidant capacity (EC50 of ethyl acetate phase (0.074 ± 0.01 mg/mL) > ethanol phase (0.136 ± 0.03 mg/mL)). Both extracts showed antimicrobial activity, especially against Gram-positive Streptococcus pyogenes and Staphylococcus aureus bacilli strains, the ethyl acetate phase being more active. Regarding the in vitro antitumor test, the results revealed a dose-dependent cytotoxic effect against A375 melanoma cell lines, more pronounced in the case of the ethyl acetate phase. In addition, the ethyl acetate phase stimulated the proliferation of human keratinocytes (HaCaT), while this effect was not evident in the case of the ethanolic phase at 24 h post-stimulation. Consequently, G. verum l. could be considered a promising phytocompound for the antitumor approach of cutaneous melanoma.